IMPROVING STUDENTS' PHYSICAL FITNESS THROUGH THE USE OF COMBINED SPORTS GAMES (Physical Culture and Sport: Scientific Perspective, 2024)
The article is dedicated to the search for effective ways to improve the physical fitness of students. The attitude of students towards the implementation of combined sports games during academic physical education classes as a means of developing physical qualities has been identified, and the monitoring of their development has been conducted. Based on a survey of 50 students from the main medical group (25 males and 25 females), a positive impact of physical exercises on the formation of professionally important physical qualities has been established (68.4% - males and 84.0% - females). The importance of developing all physical qualities in student age is emphasized by 72.0% of males and 58.0% of females. However, 53.2% of males and 76.3% of females indicated that they have a satisfactory level of physical fitness, confirming the need to improve physical education for students through the introduction of innovative approaches, namely combined sports games.A pedagogical experiment involving 83 first and second-year students (42 first-year students, 21 males, and 21 females, and 41 second-year students, 20 males, and 21 females) was conducted to monitor physical fitness using combined sports games. Each session included games such as volleyball-tennis (fistball), korfball-football, handball-football, focusing on the development of speed, speed-strength qualities, flexibility, and agility. It was found that the highest interest among first and second-year students is in sports games, with 58.8% of males and 53.2% of females expressing interest. Among males, 33.7% want to engage in volleyball, 49.4% in korfball, 44.1% in handball, and 68.7% in football. Among females, 56.0% want to play volleyball, 24.0% football, 38.5% korfball, and 22.4% handball.The introduction of combined sports games more positively influences the development of physical qualities in males than females. However, it is worth noting that the means of combined sports games were less effective for the flexibility development of males, both in the first and second years. Significant improvements in physical fitness indicators were observed in first-year males: speed qualities by 3.95%, speed-strength by 5.06%, agility by 0.28%; and second-year males: speed-strength qualities by 12.35%, agility by 0.49%. For females, a significant increase in indicators was found only in the second year: flexibility by 3.1%, agility by 0.36%.
Keywords: students; physical education; physical qualities; combined sports games